Immunohistochemical characterization of prototypical endometrial clear cell carcinoma—diagnostic utility of HNF‐1β and oestrogen receptor. Issue 4 (7th December 2013) - Hoang, Lien N; Han, Guangming; McConechy, Melissa; Lau, Sherman; Chow, Christine; Gilks, C Blake; Huntsman, David G; Köbel, Martin; Lee, Cheng‐Han
<x xml:space="preserve">Abstract</x> Aims The great majority of ovarian clear cell carcinomas have a hepatocyte nuclear factor 1 homeobox B (HNF‐1β)‐positive and oestrogen receptor (ER)‐negative immunoprofile. However, the pattern of HNF‐1β and ER immunostaining in clear cell carcinomas of the endometrium and the usefulness of this panel in distinguishing clear cell carcinoma from other histological types of endometrial carcinoma have yet to be well defined. Methods and results We examined the immunostaining patterns of HNF‐1β, ER and p53 in 15 morphologically classic pure endometrial clear cell carcinomas, and compared these patterns with 15 endometrioid and 15 serous carcinomas of the endometrium. We observed the presence of diffuse (>70%) moderate to strong nuclear HNF‐1β staining and negative ER staining in 14 of 15 clear cell carcinomas, with the remaining case showing both diffuse strong nuclear HNF‐1β staining and focal ER staining. In comparison, only one of 15 serous carcinomas and none of 15 endometrioid carcinomas showed a combination of diffuse moderate to strong HNF‐1β nuclear staining and negative ER staining. Aberrant p53 immunostaining was observed in five of 15 (33%) clear cell carcinomas. Conclusions Overall, our findings demonstrate that, similarly to the situation for the ovary, a diagnostic panel of HNF‐1β and ER may be considered for separating clear cell carcinoma from endometrioid and serous carcinoma of the endometrium.